ANALISIS PENGARUH RASIO-RASIO CAMEL SEBAGAI PENILAIAN TINGKAT KESEHATAN BANK TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK JAKARTA - Fariz Abdullah; L. Suryanto (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
Analysis was needed for portfolio investment in capital market to understand rate of return and risk in that investment. Stock price volatility has influence on stock return in capital market. Using public banks in Jakarta Stock Exchange during 1997-2001, this research was conducted to understand impact of CAMEL (CAR, ALR, NPM, ROA, and LDR) on stock price.  Multiple regression analysis result: (a) there is significant and positive impact of CAR, ALR, and NPM on stock return, (b) there is significant and negative impact of LDR on stock return.Key Words : Banking Industries; Invesment; Stock Price; CAMEL